2010
DOI: 10.1089/hum.2010.006
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Transplantation of Endothelial Progenitor Cells Genetically Modified by Adeno-Associated Viral Vector Delivering Insulin-Like Growth Factor-1 Gene After Myocardial Infarction

Abstract: The regenerative potential of bone marrow-derived endothelial progenitor cells (EPCs) has been adapted for the treatment of myocardial and limb ischemia via ex vivo expansion. We sought to enhance EPC function by the efficient genetic modification of EPCs in a rat model of myocardial infarction. Peripheral blood EPCs were expanded and transduced, using adeno-associated virus (AAV). AAV-mediated EPC transduction efficacy was 23 ± 1.2%, which was improved by 4.0- to 7.2-fold after pretreatment with the tyrosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 37 publications
5
24
0
Order By: Relevance
“…These results are consistent with previous ones demonstrating that several cytokines, released by peripheral blood or bone marrow-derived EPC, are potent inhibitors of apoptosis (39)(40). Furthermore, a recent study by Sen et al (41) showed that autologous transplantation of the genetic modification of EPCs also inhibited cardiac apoptosis in a rat model of myocardial infarction. Collectively, results in the current study confirmed previous findings demonstrating that cardiomyocytes apoptosis is associated with the progression of DCM, and that EPC implantation has the potential to prevent cardiomyocytes apoptosis in diabetic conditions.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous ones demonstrating that several cytokines, released by peripheral blood or bone marrow-derived EPC, are potent inhibitors of apoptosis (39)(40). Furthermore, a recent study by Sen et al (41) showed that autologous transplantation of the genetic modification of EPCs also inhibited cardiac apoptosis in a rat model of myocardial infarction. Collectively, results in the current study confirmed previous findings demonstrating that cardiomyocytes apoptosis is associated with the progression of DCM, and that EPC implantation has the potential to prevent cardiomyocytes apoptosis in diabetic conditions.…”
Section: Discussionsupporting
confidence: 92%
“…This method has been tested in animal models of ischemia using exogenous delivery of VEGF165 [98], insulin-like growth factor-1 [99], HO-1 [100], or other genes to diferent types of cells: AD-MSC, EC, BM-MSC, etc. In majority of reports, modiication resulted in improvement of response after delivery to ischemic tissue.…”
Section: Cell Therapy and Ex Vivo Modiied Cellsmentioning
confidence: 99%
“…We have previously demonstrated the use of genetically modified rat EPCs to treat myocardial infarction (MI)-related complications in Sprague-Dawley rats. Adeno-associated virus (AAV) mediated IGF-1 expression reportedly increased cardiac function by increasing cardiomyocyte proliferation and capillary density in the myocardium and by decreasing cardiomyocyte apoptosis in a myocardial infarction rat model [7]. Both adenovirus and recombinant AAV are DNA virus which, remains as an episomal character without integrating with host genome.…”
Section: Endothelial Progenitor Cellsmentioning
confidence: 99%